Peranan Keluarga dalam Mengatasi Kenakalan Remaja - Najamudin (EduInovasi: Journal of Basic Educational Studies, 2024)
Juvenile delinquency is one of the social problems that continues to be a concern in various societies. Families have an important role in overcoming this phenomenon. This research aims to explore the role of family in overcoming juvenile delinquency through literature review as well as by using descriptive analytical method by collecting data from various sources relevant to the topic. Various literature sources were used to investigate various aspects of the family's role, including providing affection, modeling, establishing effective communication, setting boundaries, providing emotional support, encouraging positive activities, moral and ethical education, and cooperation with educational institutions and the community. The results show that families that have good relationships, open communication, and provide positive support can help reduce juvenile delinquency rates. Therefore, it is important for families to understand their role in guiding and supporting adolescents in facing social challenges. Families play an important role in shaping adolescent character and behavior. The role of parents in educating children must be emphasized so that children have strong moral principles and are not tempted to commit delinquency. In shaping children's character, parents must have good communication with children, provide attention and affection, and provide examples of good behavior. In addition, families can also teach children about ethics, norms and values that apply in society. With a strong family role, it is expected to reduce the problem of juvenile delinquency in society.